Synthesis and characterization of Mn–ZnFe2O4 and Mn–ZnFe2O4/rGO nanocomposites from waste batteries for photocatalytic, electrochemical and thermal studies. (16th November 2017) - Mylarappa, M; Venkata Lakshmi, V; Vishnu Mahesh, K R; Nagaswarupa, H P; Raghavendra, N
Abstract: In the present paper, Mn–ZnFe2 O4 and Mn–ZnFe2 O4 /rGO composites recovered from waste batteries using acid dissolution and ferrite processing were studied. The recovered Mn–ZnFe2 O4 nanocomposites were decorated onto rGO using the facile hydrothermal method. The recovered material was characterized using x-ray powder diffraction to study the particle size and crystallinity. The morphology of the composites was analyzed using scanning electron microscopy, and elements present in the materials were studied using energy dispersive x-ray analysis. The functional groups attached were observed using a Fourier transform infrared spectrometer. Furthermore, the recovered composites were evaluated in thermal studies using thermal gravimetric analysis, differential scanning calorimetry and dynamic thermal analysis. The material was used as a photocatalyst for the removal of acid orange 88 dye, and as an electrocatalyst. The decreased band gap energy for the Mn–ZnFe2 O4 /rGO composite was displayed in better photocatalytic activity for a given reaction. The electrochemical properties of Mn–ZnFe2 O4 and Mn–ZnFe2 O4 /rGO have been investigated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) with a paste-type electrode. The CV indicated the reversibility of the electrode reaction, and the EIS revealed that a decrease in the charge transfer resistance increases the double layer capacitance of the rGO/Mn–ZnFe2 O4 electrode.